Risk mitigation approaches for improved resilience in distribution networks - Leite, Jonatas Boas [UNESP]; Kezunovic, Mladen (Institute of Electrical and Electronics Engineers (IEEE), 2020)
traditionally the risk analysis framework comprises two steps: risk assessment and risk mitigation. The tracking of operating conditions for each feeder section of a distribution network using the prediction of hourly risk levels and monthly accumulated risks corresponds to the first step. In this paper, we evaluate the use of two modern approaches to risk mitigation, one commonly named as automatic fault location, isolation and service restoration (FLISR), and other as demand response management (DRM). Since the implementation of these approaches depends on distribution automation, the control actions to mitigate the risk are carried out through the distribution management system. Results reveal advantages in the implementation of FLISR and DRM for improving the distribution network resilience. The developed visualization tool with georeferenced data from a real-world distribution network supports the achieved benefits.
Keywords: Demand Response Management (DRM); Fault Location; Isolation and Service Restoration (FLISR); Power Distribution System; Predictive Risk Assessment; Resilience; Risk Mitigation